Antenatal diagnosis of trisomy 13 with unexpected increase in alpha-feto protein. - Fitzsimmons, J S (1976)
A 24-year-old woman who had previously given birth to an infant with Down's syndrome was shown by chromosomal analysis of the liquor amnii to be carrying an infant with trisomy D. Routine examination of serum and liquor alpha-feto protein (AFP) in the antenatal period showed unexpected high levels of both, consistent with a neural tube defect. The fetus, however, did not have evidence of a neural tube defect but had scalp defects which were presumed to have allowed the leakage of AFP from the fetus into the liquor amnii and hance into the maternal serum.